The effectiveness of acupuncture in cancer pain treatment - Krukowska, Kamila; Krzyśkowska, Sylwia; Kuchta, Eliza; Rudzińska, Anna; Szklener, Katarzyna; Mańdziuk, Sławomir (Frontiers in Oncology, 2024)
IntroductionIn recent years, pain has been recognized as a primary factor significantly diminishing the quality of life in cancer patients. Recent data have prompted the establishment and increased application of non-pharmacological interventions in pain management, such as acupuncture.ObjectivesThis review assesses literature from 2018 to 2023 on the impact of acupuncture on pain management and quality of life in cancer patients, with a particular focus on reducing pain intensity. The effectiveness of acupuncture therapy was compared with the traditional treatment of pain symptoms, with a focus on the patients’ quality of life.ConclusionsAlthough no conclusive scientific evidence confirms the effectiveness of acupuncture in treating cancer pain symptoms, numerous studies have demonstrated its ability to reduce pain, better control pain, decrease analgesic intake, and significantly improve patients’ quality of life. Further research is needed to unequivocally confirm the clinical benefits of acupuncture.